Salter osteotomy without open reduction in the Tonnis type II developmental hip dysplasia: A retrospective clinical study - Gurger, Murat; Demir, Sukru; Yilmaz, Mehmet; Once, Gokhan (Sage Publications Ltd, 2019)
Purpose: We aimed to evaluate the clinical and radiological outcomes of children older than 18 months who were treated with Salter osteotomy without open reduction for Tonnis type II hip dysplasia. Methods: Thirty-two type II hips of 24 patients were included in the study. The mean age was 43.22 (18-108) months. The mean follow-up period was 50 (24-142) months. Seven patients had left sided, nine had right sided, and eight had bilateral developmental dysplasia of the hip. All patients underwent closed reduction and Salter osteotomy. Preoperative and postoperative radiographs were assessed by measuring the center-edge (CE) angle of Wiberg, Smith's c/b and h/b ratio, and acetabular index (AI). Patients were evaluated clinically according to McKay's criteria and radiologically according to Severin criteria. The Kalamchi and MacEwen criteria were used in the evaluation of avascular necrosis. Results: The mean preoperative AI, CE angle, c/b, and h/b ratio were 36.7 degrees (+/- 4.1), 7.2 degrees (+/- 5.9), 0.9 (+/- 0.08), and 0.05 (+/- 0.04), respectively. The mean latest follow-up AI, CE angle, c/b, and h/b ratio were 18.2 degrees (+/- 1.7), 38.8 degrees (+/- 5.4), 0.6 (+/- 0.03), and 0.19 (+/- 0.04), respectively. The comparison of preoperative and postoperative radiological values revealed statistically significant improvement (p < 0.01). On the latest physical examinations of the patients, 25 (78.1%) hips were rated excellent, and 7 (21.9%) were rated good according to the McKay criteria. The Severin classification determined 25 (78.1%) hips were grade I and 7 (21.9%) hips were grade II. Type I avascular necrosis (AVN) was seen in four (12.5%) hips. Three of these four hips were more superolateral in preoperative radiographs (c/b > 1 and h/b < 0.05). Conclusions: Salter osteotomy without open reduction is a good surgery option for Tonnis type II hip dysplasia, in which closed reduction can be performed. However, the risk of AVN should be kept in mind in more superolateral type 2 hips.
Keywords: closed reduction; developmental dysplasia of the hip; salter osteotomy